Biaxially extended side-chain conjugation of benzodithiophene-based polymer dots for superior photocatalytic stability under visible-light irradiation. Issue 1 (February 2022) - Elewa, Ahmed M.; Jayakumar, Jayachandran; Huang, Yen-Wen; Elsayed, Mohamed Hammad; Chang, Chih-Li; Ting, Li-Yu; Lin, Wei-Cheng; Chueh, Chu-Chen; Chou, Ho-Hsiu
Abstract: Conjugated polymer dots (Pdots) based on a series of BDT-based polymers with varied biaxially extended side-chain conjugations were prepared and employed for photocatalytic hydrogen production under visible light irradiation from aqueous solutions. The BDT-based polymers consisted of a dithiophedifluorobenzo[ c ][1, 2, 5]thiadiazole (DFBT) moiety as the acceptor unit and a BDT unit with different biaxially extended side-chains, including a alkyl-monothienyl group (T), a linear alkyl-dithiophene (2T) group, a branched alkyl-terthiophene (3T) group, and a fused alkyl-benzotrithiophene (B3T) group. The as-prepared Pdots based on these four polymers (PBDT-T, PBDT-2T, PBDT-3T, and PBDT-B3T) showed varied photophysical and electrochemical properties along with distinctive photocatalytic activity and long-term stability. Among them, the PBDT-B3T Pdots were showed to deliver a high photocatalytic efficiency of 14.1 mmol g −1 h −1 and a superior photocatalytic stability over 375 h in the presence of Pt as cocatalyst and ascorbic acid as sacrificial electron donors. Our results revealed that varying the structures of the biaxially extended side-chains endows a great flexibility in the photocatalytic activity of the polymers and the biaxially-extended conjugated side-chains can be a promising design strategy for the conjugated polymer to enhance the photocatalytic activity and stability. Graphical Abstract: ga1 Introduction of biaxially extended side-chains with varying conformational isomers of thiophenes onto the BDT polymers is highly beneficial for harvesting broad absorption region resulting in high photocatalytic efficiency and robust stability. Highlights: Introduction of side-chain with varying thiophene geometry onto the polymers helps for harvesting broad absorption region. The results show that varying the side-chain have a great effect on the photocatalytic activity and stability of the polymers. PBDT-B3T Pdots were demonstrated to provide enhanced photocatalytic performance with prolonged stability to over 375h. This study manifests that the introduction of fused side-chains is highly beneficial for improving photocatalytic HER and stability.